Arabic in Movie Subtitles: Ideology, Accuracy, and Shifts in Meaning in the Series “Umar bin Khattab” - Faruqy, Muhammad Ma’ruf (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Translating film text (subtitles) from Arabic to Indonesian is not merely a matter of substituting words, but rather a process of interpreting ideology, ensuring semantic accuracy, and adapting to the evolving messages displayed on screen. The primary focus of this study is how a translator addresses the challenge of preserving the deeply rooted religious values in the historical series Umar bin Khattab, Episode 11, while navigating technical subtitle constraints that limit character count and display duration. Through a research method analyzing every dialogue during the Battle of Badr, it was found that there are frequent shifts in meaning from general terms to more specific ones. This approach was taken so that Indonesian viewers could immediately grasp the historical context without feeling confused. Additionally, it is evident that the translator’s religious perspective influenced the decision to retain original terms like “Ahad” rather than translating them, in order to preserve the sanctity and spiritual essence of the scene. The results of this study provide insight for translators of religious films that the quality of a translation is not merely measured by how closely the words match a dictionary, but by how well the message resonates with the audience’s culture. In conclusion, creative interpretation is essential to ensure that the grand historical narrative conveyed in Arabic retains its full meaning and feels close to the hearts of modern Indonesian society.